2023
DOI: 10.2174/1570193x19666220411134006
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide a Valid Scaffold for Antioxidant Drug Development

Abstract: Sulfonamides, like the well-known sulfa drugs, are ascribed to a myriad of biological activities, including antioxidant activity. In fact, several tertiary sulfonamides particularly N,N-disubstituted analogues are recognized as antioxidants being able to prevent or minimize oxidative damage that is associated in several oxidative-stress related diseases. The structural diversity of this class of compounds paved the way for drug discovery programs aimed to find therapeutic agents. Attributes such as low-cost sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…Sulfonamide derivatives have been found to activate Nrf2 and inhibit Keap1-Nrf2 protein-protein interaction thereby antagonizing oxidative stress. This results in the elimination of reactive oxygen species (ROS), alteration of glutathione homeostasis, up-regulation of the expression of antioxidant response element dependent genes and enhancement of antioxidant defence mechanism [ 1 , 109 , 110 ]. Peng and co-workers [ 111 ] reported that caffeic acid sulfonamide derivatives ( 8 , 9 , 10 ) ( Table 1 ), when used in the treatment of H 2 O 2 -stimulated A549 cells, enhance mRNA expression of Nrf2 and its target genes.…”
Section: Nrf2-activating Synthetic Organosulfur Compoundsmentioning
confidence: 99%
“…Sulfonamide derivatives have been found to activate Nrf2 and inhibit Keap1-Nrf2 protein-protein interaction thereby antagonizing oxidative stress. This results in the elimination of reactive oxygen species (ROS), alteration of glutathione homeostasis, up-regulation of the expression of antioxidant response element dependent genes and enhancement of antioxidant defence mechanism [ 1 , 109 , 110 ]. Peng and co-workers [ 111 ] reported that caffeic acid sulfonamide derivatives ( 8 , 9 , 10 ) ( Table 1 ), when used in the treatment of H 2 O 2 -stimulated A549 cells, enhance mRNA expression of Nrf2 and its target genes.…”
Section: Nrf2-activating Synthetic Organosulfur Compoundsmentioning
confidence: 99%
“…Indeed, NRF2 regulates the expression of several antioxidant enzymes such as NAD(P)H Quinone Dehydrogenase 1 (NQO1) and heme oxygenase-1 (HO-1), which are involved in xenobiotic metabolism [ 57 ], in metabolism of carbohydrates [ 58 ], lipids and iron [ 59 ], and modulates anti-inflammatory responses [ 48 ]. In vitro and transgenic model systems, as well as clinical and epidemiological studies have implicated NRF2 activity on the activation of endogenous antioxidant and cytoprotective mechanisms in the prevention and treatment of oxidative stress and inflammation-mediated diseases, including neurodegenerative diseases, cardiovascular disorders, autoimmune diseases, and lung, liver and kidney chronic diseases [ 7 , 8 , 9 , 60 , 61 ]. A large body of data consider it a paradox that NRF2 inhibits tumor initiation and cancer metastasis via the elimination of ROS and carcinogens but becomes an accomplice in helping tumor cells to withstand high level of ROS and resist apoptosis which can be referred to as the reverse side of the NRF2/KEAP1 signaling pathway.…”
Section: Biologic Effects Of Nrf2/keap1 Signaling Pathwaymentioning
confidence: 99%
“…Since the landmark discovery of prontosil, sulfonamides, the compounds derived from 4-aminobenzenesulfonamide (sulfanilamide), have long been associated with medicine and agriculture due to their broad-spectrum antimicrobial activity and inexpensive nature. 1 Conventional structure–activity relationship studies believed that the free amino group at the phenylic para -position is essential for their antibacterial action, which can be attributed to the requirement of this substituent for sulfonamides to mimic p -aminobenzoic acid (PABA) for inhibiting folic acid biosynthesis. 2 Nevertheless, with the deepening of the investigation on the structural modification of sulfa drugs, it is found that the introduction of appropriate functional groups on the phenylamino group of sulfanilamide not only could improve its antibacterial performance but is also expected to produce new pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%